Effect of different light-curing techniques on hardness of a microhybrid dental composite resin - Rastelli, Alessandra Nara de [UNESP]; Navarro, Ricardo Scarparo; Saad, José Roberto Cury [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Bagnato, Vanderlei Salvador (Editora Cubo, 2014)
Objective: This study assessed the Vickers hardness (VHN) provided by two LCUs when using (1) direct and indirect light-curing techniques, (2) 40 and 60 s and (3) top and bottom surfaces. Material & Methods: One halogen Curing Light 2500 (3M Espe) and one LED (MM Optics) were used by direct and indirect (0, 1.0, 2.0 and 3.0 mm of dental structure) techniques during 40 and 60 s. The samples were made with FiltekTM Z250 in a metallic mould with a central orifice (4 mm in diameter, 2 mm in thickness). The samples were stored in dry mean by ± 24 h and the hardness measurements were performed in a testing machine (Buehler MMT-3 digital microhardness tester Lake Bluff, Illinois USA). A 50 gf load was used and the indenter with a dwell time of 30 s. The data were submitted to multiple ANOVA and Newman-Keuls‘s test (p < 0.05). Results: Halogen LCU exhibited higher Vickers hardness values than LED mainly because of the power density used. Hardness values were influenced by LCUs, lightcuring techniques, irradiation times and surfaces. For both LCUs, hardness values were found to decrease with indirect light-curing technique, mainly for the bottom surface. Samples irradiated for 60 s exhibited higher hardness values when the halogen LCU was used. For 60 s, the VHN values were statistically significant greater than 40 s. Significant differences in top and bottom surfaces Vickers hardness number (VHN) values were observed among different LCUs used 40 and 60 s. Conclusion: The LCUs, lightcuring techniques, variations of irradiation times, and surfaces (top and bottom) influence the composite resin hardness.

Objetivo: Este estudo avaliou a dureza Vickers (VHN) em função de duas fontes de luz quando utilizadas diferentes (1) técnicas de fotoativação, direta e indireta, (2) 40 e 60 s, e (3) superfícies de topo e base. Material e Métodos: Uma fonte de luz halógena Curing Light 2500 (3M Espe) e um LED (MM Optics) foram utilizados nas técnicas de fotoativação direta e indireta (0 , 1,0, 2,0 e 3,0 milímetros de estrutura dental), durante 40 e 60 s. As amostras foram feitas utilizando-se FiltekTM Z250 em matriz metálica com orifício central (4 mm de diâmetro, com 2 mm de espessura). As amostras foram armazenadas em meio seco por ± 24 h e as medidas de dureza foram realizadas em microdurômetro (Buehler MMT-3 digital microhardness tester Lake Bluff, Illinois USA). Uma carga de 50 gf durante 30 s foi utilizada. Os dados foram submetidos à análise de variância múltipla e teste de Newman-Keuls (p < 0,05). Resultados: A fonte de luz halógena promoveu os maiores valores de dureza Vickers, principalmente, em função da densidade de potência utilizada. Os valores de dureza foram influenciados pelas fontes de luz, técnicas de fotoativação, tempos de irradiação e superfícies, topo e base. Para ambas as fontes de luz, os valores de dureza diminuíram com a técnica de fotoativação indireta, principalmente para a superfície de base. Amostras irradiadas por 60 s apresentaram valores de dureza maiores quando a fonte de luz halógena foi utilizada. Durante 60 s , os valores de VHN foram estatisticamente significativos maior do que 40 s. Diferenças significativas foram observadas nos valores dureza Vickers (VHN) para as superfícies de topo e base utilizando 40 e 60 s. Conclusão: As fontes de luz, técnicas de fotoativação direta e indireta, tempos de irradiação e superfícies (topo e base) influenciam na dureza da resina composta.
Efeito de diferentes técnicas de fotoativação na dureza de uma resina composta dental microhíbrida
Keywords: Composite resin; LED; Halogen lamp; Hardness; Photo-activation; Resina composta; LED; Lâmpada halógena; Dureza; Fotoativação